2013
DOI: 10.1371/journal.pone.0078931
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity, Chromosomal Distribution and Expression Effects of Transposable Elements in Coffea Genomes

Abstract: Plant genomes are massively invaded by transposable elements (TEs), many of which are located near host genes and can thus impact gene expression. In flowering plants, TE expression can be activated (de-repressed) under certain stressful conditions, both biotic and abiotic, as well as by genome stress caused by hybridization. In this study, we examined the effects of these stress agents on TE expression in two diploid species of coffee, Coffea canephora and C. eugenioides, and their allotetraploid hybrid C. ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…From the between-strains transcriptomic analysis, TEs again held a central role, with their expression showing strain-specificity as shown for fungi and plants [86][87][88]. The absence of specific TEs from the genomes of a couple of the strains (1189B3 and 1189A3), as well as the markedly different response to low, and for some genes, high, temperature of one of the three strains, B651, point to a high intraspecific variability.…”
Section: Discussionmentioning
confidence: 93%
“…From the between-strains transcriptomic analysis, TEs again held a central role, with their expression showing strain-specificity as shown for fungi and plants [86][87][88]. The absence of specific TEs from the genomes of a couple of the strains (1189B3 and 1189A3), as well as the markedly different response to low, and for some genes, high, temperature of one of the three strains, B651, point to a high intraspecific variability.…”
Section: Discussionmentioning
confidence: 93%
“…In the study by Madlung et al [79] noted above, despite an increase in transcriptional activity after allopolyploidy, limited transpositional activation of the Sunfish transposon in allopolyploid Arabidopsis was detected through a methyl-insensitive Southern blot analysis [79]. In polyploid coffee (Coffea arabica), microarray analysis showed that the expression level of Tip100 in allopolyploid C. arabica is higher than the sum of the expression levels of Tip100 in its parents, C. eugenioides and C. canephora [89]. FISH results showed an increase in Tip100 copy number and a more prevalent interstitial chromosomal location in allotetraploid Coffea compared with the parental species, indicating an increase in transpositional activity in this species compared with the parental species [89].…”
Section: (E) Transposons and Noveltymentioning
confidence: 99%
“…In polyploid coffee (Coffea arabica), microarray analysis showed that the expression level of Tip100 in allopolyploid C. arabica is higher than the sum of the expression levels of Tip100 in its parents, C. eugenioides and C. canephora [89]. FISH results showed an increase in Tip100 copy number and a more prevalent interstitial chromosomal location in allotetraploid Coffea compared with the parental species, indicating an increase in transpositional activity in this species compared with the parental species [89]. Thus, although novel TE activity is noted in allopolyploids in both Arabidopsis and Coffea relative to their parents, in Arabidopsis, transcriptional and transpositional activities of TEs are negatively correlated, while in Coffea they are positively correlated.…”
Section: (E) Transposons and Noveltymentioning
confidence: 99%
“…In addition, transposable elements (TE), which are major components of plant genomes, might also shape the architecture, function and expression of plant genes and genomes throughout evolution [12]. In coffee plants, albeit previous studies have shown low TE expression, they can be detected in transcriptome analyses [1314]. …”
Section: Introductionmentioning
confidence: 99%